Perception and Annoyance Due to Vibrations in Dwellings Generated from Ground Transportation: A Review. Issue 4 (December 2015) - Trollé, Arnaud; Marquis-Favre, Catherine; Parizet, Étienne
Over the past decades, the improvement of the quality of buildings regarding sound insulation has made it possible to reduce noise exposure. But this improvement has led to the increasing importance of other environmental nuisances such as vibrations. Just like noise, vibrations can also affect human health and well-being. National authorities are progressively becoming aware of the adverse effects of vibrations on human beings. One of these adverse effects is vibration annoyance. As a prerequisite for studying vibration annoyance, many research works have provided knowledge of how vibrations are perceived by human beings. But, until now, only a few large-scale studies have been carried out to gain knowledge of annoyance due to vibrations. This knowledge is of importance for public authorities in order to plan the development of transportation networks while taking account of this environmental nuisance (i.e. vibrations). Assessing vibration annoyance is a complex task that implies research work spread over various disciplines (e.g. human sciences, physics). This is why a review of knowledge in the field of vibration perception and annoyance is felt to be necessary. More specifically, this review focuses on vibration annoyance felt by inhabitants inside buildings and caused by ground transportation sources. Before dealing with the review of annoyance due to vibrations, the basics of human vibratory perception are presented. Then, annoyance due to a vibration exposure is dealt with. In particular, the way vibration exposure and vibration annoyance are measured and assessed is tackled. The main features and results of research works that aimed to establish exposure-effect relationships between annoyance and vibrations are described. Finally, this review presents a state-of-the-art of annoyance due to a combined exposure to vibrations and noise, since people exposed to vibrations are also often exposed to airborne noise. This review is non-exhaustive, but it can give to scientists and engineers working in the field tools for a better understanding of some of the factors to consider when dealing with the issue of vibration annoyance due to ground transportation.